The impact of postpartum obsessive-compulsive symptoms on child development and the mediating role of the parent–child relationship: A prospective longitudinal study - Blum, Sophie; Mack, Judith T.; Weise, Victoria; Kopp, Marie; Asselmann, Eva; Martini, Julia; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2022)
Background: The first two years of life are a particularly sensitive period for the parent-child relationship as well as a healthy, age-appropriate child development. Both have been shown to be linked to postpartum depressive and anxiety symptoms, while the role of obsessive-compulsive symptoms, which are also common, is still largely understudied. In addition, fathers have been neglected in this area of research. This study, which includes both mothers and fathers, aims to investigate the longitudinal associations between postpartum obsessive-compulsive symptoms and different domains of child development, as well as the mediating role of the parent-child relationship. Methods: Data were drawn from the prospective longitudinal study DREAM, with 674 mothers and 442 fathers from the general population completing self-report questionnaires at four measurement points. Longitudinal associations between parental postpartum obsessive-compulsive symptoms eight weeks postpartum, the parent-child relationship 14 months postpartum, and child development 24 months postpartum were investigated using regression and mediation analyses. A number of potential confounding variables were considered, i.e., age, academic degree, postpartum depressive and anxiety symptoms of the parents, preterm birth and temperament of the child, as well as COVID-19 pandemic-driven adversities. Results: When adjusting for confounders, neither maternal nor paternal postpartum obsessive-compulsive symptoms had adverse effects on the respective parent-child relationship and child development. Further, no mediating role of the parent-child relationship between parental postpartum obsessive-compulsive symptoms and child development could be confirmed. Instead, we found that the mother- and father-child relationship were differentially related to specific child developmental domains. For mothers, a poorer mother-child relationship was prospectively related to poorer fine motor development. For fathers, a poorer father-child relationship prospectively predicted a poorer overall development as well as poorer gross motor, fine motor, problem-solving, and personal-social development. Conclusions: Our results suggest that negative effects on the parent-child relationship and child development may only become apparent in full-blown postpartum obsessive-compulsive disorder. Given the differential impact on specific developmental domains, our findings also suggest that it is crucial to consider both parents in clinical practice as well as in future research, rather than focusing only on the mother-child dyad.